Research on Visual Nursing in the Context of Big Data - Wang Fengyun, Gao Juan, Li Weihong (Forest Chemicals Review, 1970)
With the development of big data technology, data fusion and analysis technology are more and more applied to visual nursing. With the emergence of unstructured massive data, the importance of big data is not only reflected in the huge amount of data, but also how to analyze and visualize massive big data to obtain more intelligent, in-depth and valuable information. This paper systematically summarizes the main internal and external characteristics of the included literature, and intuitively presents its institutional cooperation, research hotspots and development trend, so as to comprehensively understand the relevant research status of wisdom education in nursing education in China. This paper discusses the advantages and disadvantages of the application of visual analysis in the field of nursing under the background of big data, in order to provide reference for the research of visual application in the field of nursing.